Influence of Site Pairing in Hydrophobic Silica-Supported Sulfonic Acid Bifunctional Catalysts - Kasinathan, Palraj; Lang, Charlotte; Gaigneaux, Eric M; Jonas, Alain M; Fernandes, Antony E (Langmuir, 2020)
Imparting hydrophobicity to solid acid catalysts is critical to regulating their performances by allowing the creation of a less polar environment and improved partitioning of the reactants. Here we present different approaches for the preparation of silica-based catalysts comprising sulfonic acid (-SO3H) sites and hydrophobic decyl (-C10) chains by either simultaneous or sequential postfunctionalization of an azide-functionalized mesoporous silica platform. This set of hybrid bifunctional catalysts is compared in the model esterification of octanol with acetic acid, and the influence of the preparation methods together with the resulting site spatial distribution is discussed. In parallel, we show that pairing the two functional groups affords a maximum synergistic effect compared to more traditional mixed catalysts with random distributions of acid and hydrophobic functions.Imparting hydrophobicity to solid acid catalysts is critical to regulating their performances by allowing the creation of a less polar environment and improved partitioning of the reactants. Here we present different approaches for the preparation of silica-based catalysts comprising sulfonic acid (-SO3H) sites and hydrophobic decyl (-C10) chains by either simultaneous or sequential postfunctionalization of an azide-functionalized mesoporous silica platform. This set of hybrid bifunctional catalysts is compared in the model esterification of octanol with acetic acid, and the influence of the preparation methods together with the resulting site spatial distribution is discussed. In parallel, we show that pairing the two functional groups affords a maximum synergistic effect compared to more traditional mixed catalysts with random distributions of acid and hydrophobic functions.